2023
DOI: 10.1109/tem.2021.3079347
|View full text |Cite
|
Sign up to set email alerts
|

Digital “is” Strategy: The Role of Digital Technology Adoption in Strategy Renewal

Abstract: As digital technologies emerge and improve rapidly, firms face changing tradeoffs in terms of their technology infrastructure and strategic direction. Hence, many of them adopt new digital technology and develop new business models and strategies. The literature on strategic alignment of IT suggests that firms need to synchronize these different domains of choice. We therefore ask how far firms renew their strategy as they adopt new technologies. We study this question empirically by assessing if the adoption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Technological competencies, digital resources, support from top management, and organizational structure have been shown to influence an organization's decision to adopt digital technologies [6] and [35]. Van Zeebroeck et al [44] observed a strong positive association between the scope of strategy change and the stage of digital technologies adoption, suggesting the existence of a link between technological structure and strategy. Besides, management support is a critical determinant of digital technology adoption.…”
Section: ) Organizational Factors and Digital Technology Adoptionmentioning
confidence: 99%
“…Technological competencies, digital resources, support from top management, and organizational structure have been shown to influence an organization's decision to adopt digital technologies [6] and [35]. Van Zeebroeck et al [44] observed a strong positive association between the scope of strategy change and the stage of digital technologies adoption, suggesting the existence of a link between technological structure and strategy. Besides, management support is a critical determinant of digital technology adoption.…”
Section: ) Organizational Factors and Digital Technology Adoptionmentioning
confidence: 99%
“…On the contrary. Dual winners benefit more from digitization than from peers because they associate digitization with strategic renewal (Van Zeebroeck et al , 2021). An example of a dual winner is Schneider Electric, a French multinational company that specializes in digital automation and energy management; it has outperformed its peers for many years.…”
Section: The “Flying Wheel” Between Performance and Resiliencementioning
confidence: 99%
“…The adoption of digital technology in SMEs is influenced by factors such as organizational readiness, technological infrastructure, and perceived benefits of digital integration. Research has shown that the adoption of new digital technologies can lead to changes in firm strategy, with a strong positive association between the extent of strategy change and the stage of adoption of advanced digital technologies overall [11]. Additionally, the extended technology acceptance model (TAM) framework has been used to investigate the determinants of adoption of digital health apps, with perceived usefulness, attitudes, perceived self-efficacy, and perceived ease of use significantly predicting customers' intention to use digital health apps [12].…”
Section: Digital Technology Adoption In Smesmentioning
confidence: 99%